Академічна доброчесність та академічне лідерство - Резнік, Світлана Миколаївна (Національний технічний університет "Харківський політехнічний інститут", 2021)
У роботі було обґрунтовано взаємозв’язок академічної доброчесності та академічного лідерства. Проаналізовано причини порушення здобувачами вищої освіти академічної доброчесності та визначено основні напрями роботи із ними, які включають їхню мотивацію щодо додержання вимог академічної доброчесності та засвоєння відповідних цінностей; навчання культури академічної доброчесності; контроль дотримання принципів доброчесності на практиці.

The work contains substantiation of a mutual link between academic virtuen and academic leadership. The reasons for academic virtue violation by applicants for higher education have been analyzed, and the main areas of working with them have been determined. These areas include motivating them regarding observing the academic virtue requirements and acquisition of corresponding values; teaching the culture of academic virtue; the control of observing the academic virtue principles in practice.
Academic virtue and academic leadership
Keywords: професор; здобувач вищої освіти; professor; applicant for higher education